E-procurement in emerging economies theory and cases - Pani, Ashis Kumar; Agrahari, Amit 1978- (Gale virtual reference library, 2007)
"This book presents issues such as legal, technical, cultural and social analysis on e-Procurement, and offers technical and managerial solutions to professionals in different emerging economies and industries"--Provided by publisher.